Slicepedia: Automating the Production of Learning Objects from Open Corpus Content - LAWLESS, SEAMUS (Springer, 2012)
The World Wide Web (WWW) provides access to a vast array of digital content, a great deal of which could be ideal for incor- poration into eLearning environments. However, reusing such content directly in its native form has proven to be inadequate, and manually customizing it for eLearning purposes is labor-intensive. This paper introduces Slicepedia, a service which enables the discovery, reuse and customization of open corpus resources, as educational content, in order to facilitate its incorporation into eLearning systems. An architecture and implementation of the system is presented along with a preliminary user-trial evaluation suggesting the process of slicing open corpus content correctly decontextualises it from its original context of usage and can provide a valid automated alternative to manually produced educational resources.
Lecture Notes in Computer Science
The 7th European Conference on Technology-Enhanced Learning, EC-TEL 2012
PUBLISHED
Saarbrucken, Germany
Keywords: Slicing; Open Corpus Content; Adaptive Hypermedia